Kulturen des Reparierens Dinge - Wissen - Praktiken - Krebs, Stefan; Schabacher, Gabriele; Weber, Heike (Edition Kulturwissenschaft, 2018)
In the 'life' of technical objects and infrastructures repair and maintenance are central practices, both economically and culturally. This book foregrounds these activities, rarely examined until now, and looks into the forms of knowledge of different cultures of repair. In the process, the expertise and political ambitions of human actors receive as much consideration as the internal dynamics of the objects themselves. The articles focus on practices such as watch or computer repair, as well as on spaces such as the home, the hospital, the Repair Cafe, and the city of the 'Global South'. In addition, the book also investigates the extent to which repair and repair-friendly design can contribute to more sustainability.